Comparison of Moderation Interpretation of Religious Mufassir in Social Media (Qs Al-Mumtahanah (60): 8-9, the perspective of Guz Dhofir and Dr. Firanda): Komparasi Tafsir Moderasi Beragama Mufassir di Media Sosial (Qs Al-Mumtahanah (60): 8-9, perspektif Guz Dhofir dan Dr. Firanda) - Minhatul Maula (Journal of Multidisciplinary Science, 2023)
This paper repeats the concept of religious moderation in Qs al-Mumtahanah (60): 8-9 based on two figures who are active on social media and are popular with students or the general public. The two figures are KH Dhofir Zuhry, known as Gus Dhofir and Dr. Firanda Andirja who comes from Indonesia and is one of the regular speakers at the Nabawi Mosque, Medina. The author uses a comparative method in analyzing the concept of religious moderation from the two figures. According to these two figures, we should apply religious moderation because the Prophet himself also gave an example during his lifetime and the Qur'an also reaffirms these concepts. However, there are important points in this religious moderation as recommendations and prohibitions in a regulation. In Qs. Al-Mumtahanah (60): 8-9, Allah only allows being moderate to people who do not disturb us and do not expel us because of differences, both in terms of religion, social, race, language and so on, this also applies to something to the contrary. So we have to be moderate if he also has the attitude and awareness of the importance of moderation. By adopting this moderation attitude, we can go deeper into creating a peaceful and prosperous environment.